2015
DOI: 10.1016/j.bbrep.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Basal cells express functional TRPV4 channels in the mouse nasal epithelium

Abstract: Basal cells in the nasal epithelium (olfactory and airway epithelia) are stem/progenitor cells that are capable of dividing, renewing and differentiating into specialized cells. These stem cells can sense their biophysical microenvironment, but the underlying mechanism of this process remains unknown. Here, we demonstrate the prominent expression of the transient receptor potential vanilloid type 4 (TRPV4) channel, a Ca2+-permeable channel that is known to act as a sensor for hypo-osmotic and mechanical stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Sonic hedgehog-positive cells are precursors for all taste cell types within taste buds 21 . It has been previously reported that TRPV4 is expressed in keratin 14-positive epidermal keratinocytes and in the olfactory and airway epithelia 22,23 . In this study, we also observed TRPV4 immunoreactivity in keratin 14-positive basal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…Sonic hedgehog-positive cells are precursors for all taste cell types within taste buds 21 . It has been previously reported that TRPV4 is expressed in keratin 14-positive epidermal keratinocytes and in the olfactory and airway epithelia 22,23 . In this study, we also observed TRPV4 immunoreactivity in keratin 14-positive basal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…TRPV4 has been identified as a key regulator of mechanically evoked cellular volume regulation, barrier permeability and immune interactions in lung, bladder, esophagus, skin, gut, kidney, choroid plexus, retinal pigment, and ciliary body epithelia. [17][18][19][20][21][22][23] TRPV4-mediated calcium influx has been linked to cytoskeletal reorganization, cell adhesion, formation of focal adhesions, and adenosine triphosphate (ATP)-dependent modulation of afferent excitation in epithelia, 5,19,24,25 yet mechanisms of TRPV4 gating are both celltype and context-specific, [26][27][28][29] and the properties of TRPV4 activation in native CECs have not been conclusively established. In this study, we employed imaging, electrophysiological, and molecular approaches to characterize calcium regulation and ATP release in CECs exposed to TRPV4 agonists, strain, volume, and temperature increases.…”
mentioning
confidence: 99%